Assessment of personal economic security in the Voronezh region - L. N. Chaykovskaya (Vestnik Voronežskogo Gosudarstvennogo Universiteta Inženernyh Tehnologij, 2022)
The economic security of the individual is an important structural component of the economic security of the region and the state as a whole. In this regard, the issues related to the assessment of the level of economic security of the individual are brought up to date. The article outlines the methodology for calculating the integral indicator of personal economic security. Based on the key human needs, six blocks of indicators have been singled out: food security, housing security, demographic potential and health care, financial security of the individual, the level of labour stability, education and spiritual enlightenment. Within each block quantitative criteria are selected to assess personal economic security in the given sphere. When calculating the integral indicator of personal economic security, it is recommended to take into account the significance of the selected blocks. The significance of the blocks may differ by region and is determined using expert methods. The proposed approach was tested in the assessment of personal economic security in the Voronezh region. The source data for the calculation was official statistical information for the Voronezh region. Defining the outline of personal economic security allows us to highlight problem areas that require special attention when ensuring the region's economic security. The calculations carried out allow us to conclude that the area that requires special attention when ensuring economic security of the Voronezh region is "demographic potential and health care". The calculated integral index of personal economic security of the population of Voronezh region allows us to state that the level of personal economic security in the region is higher than the average for the subjects of the Russian Federation and is at a favorable level. Thus, the proposed methodology for assessing the level of economic security of individuals, allows the regions to see the potential threats in the selected blocks of personal economic security and to provide for measures to neutralise them.